Foot rotation and the risk of falls in older women: A cross-sectional study - Kasović, Mario; Štefan, Lovro; Zvonar, Martin (PloS one, 2020)
Although previous evidence has shown that deviated foot structure and function are associated with falls, little is known of the association between foot rotations and falls in apparently healthy older adults. Therefore, the main purpose of the study was to determine the associations between foot rotation and falls. In this cross-sectional study, we recruited 120 older women (mean±SD; age 71.01±6.77 years; height 158.92±21.41 cm; weight 70.29±12.97 kg; body-mass index 26.79±4.42 kg/m2). Foot rotations were assessed by using pressure platform (Zebris manufacturer, Munich, Germany), while the risk of falls was assessed by using Downtown Fall Risk Index questionnaire. Correlations and multiple regression models were applied to calculate the associations. In unadjusted model, higher foot rotation was associated with higher risk of falls (β = 0.14, p<0.001 for both feet). In a model adjusted for age, body-mass index, foot pain and fitness index, higher foot rotation remained associated with higher risk of falls (β = 0.10, p<0.001 for both feet). Our study shows that older adults with higher foot rotation are at higher risk of falls. Special interventions aiming to correct for deviated foot function in older women are warranted.
Keywords: bolest; Sex Factors; Pain; Humans; index tělesné hmotnosti; Body Mass Index; Female; rizikové faktory; Aged; věkové faktory; senioři; lidé; Accidental Falls; noha (od hlezna dolů); sexuální faktory; ženské pohlaví; úrazy pádem; Cross-Sectional Studies; Foot; Age Factors; průřezové studie; Risk Factors